2015
DOI: 10.5114/bta.2015.56574
|View full text |Cite
|
Sign up to set email alerts
|

Somatic embryogenesis and genetic uniformity of regenerated cassava plants from low-temperature preserved secondary somatic cotyledons

Abstract: Low plant regeneration and transformation frequencies in cassava have been attributed to recycling of cassava secondary somatic embryos for long periods. This study examined the suitability of low-temperature storage of dehydrated cassava secondary somatic embryos as an alternative short-term conservation approach to recycling. The study included two experiments: in the first one, somatic embryogenesis from cotyledons of dehydrated secondary somatic embryos stored at six temperatures for 4, 8 and 12 months was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 31 publications
(49 reference statements)
0
2
0
Order By: Relevance
“…Isolated secondary embryos were transferred to fresh BM supplemented with 2% mannitol, 2% sorbitol, 4% mannitol, 4% sorbitol, 2% mannitol + 2% sorbitol, 2% mannitol + 4% sorbitol, 4% mannitol and 2% sorbitol and a control (free of osmotic agents) for 8 and 16 months in the dark at 16 0 C. Preliminary studies have shown that storage at 16 0 C was the most suitable low temperature for a short-term preservation of cassava secondary somatic embryo (Opabode et al 2015).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Isolated secondary embryos were transferred to fresh BM supplemented with 2% mannitol, 2% sorbitol, 4% mannitol, 4% sorbitol, 2% mannitol + 2% sorbitol, 2% mannitol + 4% sorbitol, 4% mannitol and 2% sorbitol and a control (free of osmotic agents) for 8 and 16 months in the dark at 16 0 C. Preliminary studies have shown that storage at 16 0 C was the most suitable low temperature for a short-term preservation of cassava secondary somatic embryo (Opabode et al 2015).…”
Section: Methodsmentioning
confidence: 99%
“…The molecular technique of RAPD was used to determine the genetic stability of the regenerated plants as described by Opabode et al (2015). A total of eight random decamer primers (Operon Tech, Alameda, USA) from B, C, D, and E series (OPB06, OPB08, OPB12, OPC01, OPC02, OPC05, OPC06, OPE19) were used for RAPD analysis.…”
Section: Methodsmentioning
confidence: 99%